RAQAMLI JURNALISTIKA VA MEDIA TRANSFORMATSIYASI: INTERNET VA MOBIL TEXNOLOGIYALARINING JURNALISTIKAGA TA’SIRI (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The article analyzes the process of digital journalism and media transformation. The development of the Internet and mobile technologies has affected journalism, the main differences between traditional and online journalism, and the main ethical issues arising in digital journalism are considered. In particular, such pressing issues as fake news, copyright, privacy, and information bias are analyzed from a scientific point of view. The article concludes with the importance of technologies in modern journalism and recommendations for their effective use.